Istikhdamu Wasilati Froggy Jump fi Tanmiyati Dafi’iyati Atta’alum Linnahwi wa as Shorfi bimadrosah al‘Aliyah al Islamyiah al Hukumiyah ar Robi’ah Jombang - Siti Rahma; Siti Durrotun Naseha (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This descriptive qualitative study investigates how Froggy Jump, an Educaplay-based game, was implemented to strengthen motivation in learning nahwu and sharf and how students’ motivation changed after its use at State Islamic Senior High School 4 Jombang. The study involved one Arabic teacher and 33 students of class X-H; two students were purposively selected as class representatives for interviews. Field data were collected in January 2026 through non-participant classroom observation, semi-structured interviews (students on 14 January and the teacher on 15 January), and documentation consisting of attendance records, teaching materials, lesson documents, and activity photographs. Data were analyzed through reduction and coding, thematic display, and conclusion drawing/verification, while credibility was checked through methodological triangulation. The study’s original contribution lies in adapting Froggy Jump—normally played individually—into group-based formative assessment using only one laptop and a projector in a device-limited nahwu–sharf classroom. The implementation comprised preparation of questions, teacher explanation, group competition, immediate feedback, and rewards. Before the intervention, the teacher described motivation as “very low,” while students characterized nahwu and sharf as “boring, difficult, and complicated.” After implementation, observation and interview evidence showed more focused listening, active discussion and answering, competitive persistence, enjoyment, greater effort to understand the material, and reduced boredom and drowsiness. These findings indicate that Froggy Jump functions not merely as entertainment, but as an external motivational stimulus and a formative reinforcement tool that increases engagement in rule-based Arabic learning